Studi Komparasi Penerapan Product Liability di Indonesia dan Turki - Nadine Rayna Salsabila (Fakultas Hukum, Universitas Warmadewa, 2024)
Each basic right must be fulfilled for each consumer from different countries. The creation of the Consumer Protection Law occurred because of the awareness of consumer protection. Indonesia implements this law through Law No. 8 of 1999 and Turkey through Law No. 4077 which has been amended. One of the consumer's rights is the right to get compensation if the goods sold do not have the desired quality. In the article regarding the implementation of Product Liability in Indonesia and Turkey, there are still many things that can be studied. This research will use a comparative approach and comparative law between Indonesia and Turkey. The comparative law approach in the observation of normative law not only provides knowledge, but also simply reveals descriptive knowledge, the comparative law approach in the observation of law must be able to describe in depth the legal system of other countries regarding the obstacles observed in solving the obstacles observed in solving a legal problem that is the subject of normative observation. Thus, overall it is clear that the regulations in Indonesia that regulate obligations and prohibitions of business actors emphasize the protection of consumer rights. Meanwhile, Turkey establishes the principle of responsibility of producers and sellers in ensuring safe and quality products.